DETERMINING STRIPPING RATIO LEVEL IN OPTIMIZING PRODUCTION COST AS THE OPTIMIZATION OF TOTAL PRODUCTION COST OF COAL OPEN MINING OF PT.MEGA PRIMA PERSADA (Site Visit on Coal Industry in Sanga-Sanga, East Kalimantan, Indonesia) - RICARDO (NIM : 29107387); Pembimbing : Ir. Uke MPP. Siahaan, MBA, MAXIMILLIAN
East Kalimantan is one of IndonesiaÃ‚Â’s provinces that has a significant mineable coal resource and also could be mined easily with opn pit method. This province are also have many rivers facilitating for coal distribution a it is cheaper than those with ground transport. Estimated coal reserves in East Kalimantan is approximately 14,62% from 90.5 billion metric ton of total indonesian coal reserves. At present productivity rate, indonesian coal could be mined up to 150 years. The main problem happened at this moment is a decreasing coal price at the market. It made miners can not afford to increase their productivity output (coal) because the total cost will exceed and diminish the expected gross profit while the coal offering price continue to decline. There are several parameters that influence the change of stripping ratio. Two of them are coal price index based on Indonesian Coal Index and also fluctuating production cost which mainly contributed by fuel price published biweekly. This final project analyzed various stripping ratio based on cost structure calculation which then will be compared with coal price at the real market in coal industry, to estimate the most appropriate mining operation level for PT.Mega Prima Persada. The strategy of coal mining operation level analysis in this final project is tended on the spot contract with customer. The consideration of using this strategy toward short contract is caused by proposed coal price fluctuation in the short period. According to that consideration so the adjustment of this operation level strategy will be held and proposed monthly. Cost structure calculation applied toward various operation level determined by stripping ratio, considered to coal price at the market. Result of analysis showed that the optimum operation level that was still brought feasible profit in April and May 2009 on coal price range in April 2009 is 1 : 8 with average 64% contribution from variable cost.